Acid Mine Drainage Treatment ù Reducing Costs by Enhancing Carbonate Usage (The Australasian Institute of Mining and Metallurgy, 2002)
Neutralisation, normally using lime, is the most widely used method for treating high flows of acid mine drainage (AMD). Lime costs can be very high however. If carbonate sources could be used to achieve pH values above six, costs could be greatly reduced. For example, use of locally quarried limestone at Mt Lyell could potentially reduce alkali costs from about $A 3.5 to $A 1 million/year. Methods for enhancing the effectiveness of limestone and magnesite for neutralising Mt Lyell and Savage River AMD respectively have been examined through a series of investigations. Small-scale testwork found that the maximum pH economically achievable with ground limestone was about five, due to slow dissolution rates and surface armouring. The problems of surface armouring were greatly reduced by the use of crushed limestone or magnesite at high pulp densities (75 per cent solids w/w), enabling pH values >6 to be achieved in a practical time frame. The use of particle sizes in the range 6 mm and finer also reduces costs by avoiding the need for grinding, and reduces the problems of solid-liquid separation and solid recycling that arise if large additions of ground carbonate are used. Pilot scale tests were carried out using tumbling drum reactors with limestone and Mt Lyell AMD and a pulsed-bed static reactor with magnesite and Savage River AMD. pH values averaging 6.2 and 6.4 were achieved with Mt Lyell and Savage River AMD respectively. Approximately 80 per cent of feed acidity was neutralised. A preliminary engineering design and cost estimate has been completed on the pulsed-bed reactor and shows that the concept is technically feasible and, if results are confirmed, economically attractive. Further pilot testing is planned.